1988
DOI: 10.1088/0022-3727/21/10/015
|View full text |Cite
|
Sign up to set email alerts
|

The two-stage increase in negative pressure with repeated cavitation for water in a metal Berthelot tube

Abstract: The authors made a stainless steel tube with a copper plug to study the effects of cavitation history on negative pressure for a system of water in a metal Berthelot tube. The water and the copper plug were pre-treated for air purging. The system was alternatively heated and cooled over appropriate temperature ranges many times. In the Berthelot method, the negative pressure generated with failing temperature becomes highest just before cavitation for a single heating and cooling procedure (one temperature cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Since then, several methods [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have been developed to generate negative pressures in liquids. The attainable negative pressure can be even of a few hundreds of Mpa [4,23].…”
Section: Experimental Observations Of Negative Pressure In Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, several methods [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have been developed to generate negative pressures in liquids. The attainable negative pressure can be even of a few hundreds of Mpa [4,23].…”
Section: Experimental Observations Of Negative Pressure In Liquidsmentioning
confidence: 99%
“…This is because a high pre-pressurization both promotes the disappearance of trapped gas bubbles in the crevices of the walls and helps to diffuse dissolved gas in the liquid. An even more efficient approach [21,22] uses many cycles of pressurizationdepressurization.…”
Section: Experimental Observations Of Negative Pressure In Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were degassed and kept in a vacuum chamber at around 200 C under 10 À1 Pa. Before use, a pre-degassed plug was heated in boiling water for 30 min to exhaust most of the surfacing continuous boiling sites, since they would be the weakest cavitation nuclei after sealing. 3,5,9) 8CB was supplied by Fluoromaterial. Its gel permeation chromatography (GPC) purity is 99.6%, and no further purification was attempted.…”
Section: Apparatuses and Procedures 221 Preparation Of 8cb/tube Systemmentioning
confidence: 99%
“…Our experiments showed that (i) cavitation nuclei are gases (air) trapped within tiny ''crevices'' in the metal wall of the tube, (ii) they are exhausted by repeated cavitation events induced by temperature cycles, and (iii) they can be replenished by impurity gases in the bulk of the metal wall. 3,4) Degassing pretreatment for the metal parts yielded À150 bar for water only after ca. 2000 temperature cycles, 5) while their surface pretreatments improved the increasing trends in the negative pressure for earlier temperature cycles; however, the final values rarely exceeded À110 bar.…”
Section: Introductionmentioning
confidence: 99%